2008
DOI: 10.1203/pdr.0b013e318165b8d1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Erythropoietin mRNA and Protein Concentrations in the Developing Human Eye

Abstract: Erythropoietin (Epo) is an erythropoietic, neurotropic, and angiogenic factor, and may be involved in retinal development. Studies in adult diabetic retinopathy patients reveal significantly elevated vitreal Epo concentrations. It is unknown whether Epo plays a similar role in retinopathy of prematurity. We sought to determine whether Epo is present in the normally developing human eye. Fetal serum and vitreous samples were obtained from 12 to 24 wk gestation. RNA was extracted from isolated retina for Epo mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
(40 reference statements)
1
16
0
Order By: Relevance
“…In recent years, a study reported that there is a direct correlation of fetal retina EPO mRNA amount in vitreous humor with increasing gestational age. 13 This is further supported by Wu et al 14 on the involvement of EPO in the development of human eye. During the process of organogenesis in the eye, they discovered the expression of EPO, along with signal transducer activator-of-transcription (STAT)-5, EPOR, and pro-apoptotic protein Bcl-2-associated X (Bax) expressions throughout the lens and retinal development.…”
Section: The Role Of Epo In the Eyementioning
confidence: 59%
See 3 more Smart Citations
“…In recent years, a study reported that there is a direct correlation of fetal retina EPO mRNA amount in vitreous humor with increasing gestational age. 13 This is further supported by Wu et al 14 on the involvement of EPO in the development of human eye. During the process of organogenesis in the eye, they discovered the expression of EPO, along with signal transducer activator-of-transcription (STAT)-5, EPOR, and pro-apoptotic protein Bcl-2-associated X (Bax) expressions throughout the lens and retinal development.…”
Section: The Role Of Epo In the Eyementioning
confidence: 59%
“…Following to the previous outcomes, 13,14 several studies further identified EPO in neural retina differentiation. Alternatively, EPO could facilitate the differentiation through binding with a heterodimer complex, consisting of EPOR and interleukin beta-common receptor (βcR; CD131).…”
Section: The Role Of Epo In the Eyementioning
confidence: 61%
See 2 more Smart Citations
“…1 An increasing number of studies have demonstrated the neuroprotective effects of EPO and its receptor, by anti-apoptotic mechanisms. Several studies have indicated that EPO can protect photoreceptor cells from the effects of lightinduced and hereditary retinal dystrophy; [2][3][4][5] protect retinal neurons from ischemiareperfusion injury, 6 and retinal ganglion cells after acute and chronic ocular hypertension; [7][8][9] promote ganglion cell survival and axonal regeneration after optic nerve transection; [10][11][12] attenuate inflammation in multiple sclerosis optic neuritis; 13,14 reduce the permeability of the retinal barrier and protect retinal neurons in diabetic retinopathy; [15][16][17][18] relieve diabetic macular edema; 19 enhance the stability of hypoxic retinal vessels; 20,21 and has a neuroprotective role in pigment epithelial cells subjected to photo-oxidative damage. 22 EPO exerts its biological effects through interaction with EPO receptor (EPOR).…”
Section: Introductionmentioning
confidence: 99%